PENGARUH KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN, KETEGASAN SANKSI DAN KEWAJIBAN MORAL TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK REKLAME (Studi Kasus Dinas Pendapatan Daerah Kota Pekanbaru) - Kristina -; Zirman -; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Advertisement tax is one source of revenue continues to increase revenues by increasing numbers of businesses due to economic growth. Public awareness of the obligation to comply with the applicable taxation plays an important role in tax revenues. The purpose of this study was to analyze the effect of taxpayers awareness, quality of service, tax firmness sanction and moral obligation of tax authorities against tax compliance in paying taxes on advertisement in Revenue Service Pekanbaru Area. The data was collected using a questionnaire with convenience sampling technique and used a sample of 80 taxpayers advertisement. Analysis using multiple linear regression analysis, which is processed using SPSS for windows version 17.0. The results showed that the taxpayer awareness, quality of service, tax firmness sanction and moral obligation effect on tax compliance in paying taxes on advertisement in Revenue Service Pekanbaru Area. Independent variables on tax compliance advertisement has contributed 88,8 percent, while 11,2 percent are influenced by other factors outside the model.Keywords: taxpayer compliance, taxpayers awareness, quality of service, tax firmness sanction and moral obligation.